Jumbo with students sitting at a table (Tufts Archival Research Center, 2005)
8 x 10; Students are: standing l-r: Ernest Harmon, Edmund Johnson, Jr., Priscilla Peirce, and Richard Cooke; seated, Muriel Manson, Mildred Listernick, Martha Henderson, and Lena Kofos. This date is approximate